Pendidikan Islam dan Kemajuan Sains: Historisitas Pendidikan Islam yang Mencerahkan - Masduki, Masduki; Masduki (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2015)
Islamic education-both as an institution and subject in public schools-currentlyfacing the serious and complicated challenge, for example the uncertainty ofdichotomiousparadigm. This uncertainty appears influenced strongly by theparadigm of thinking that tends to dualistic-confrontative. A paradigm thatdistinguishes the two things that seem diametrically opposed and potentially causeconflict. In Islamic education discourse, known terminology such as religiouseducation and general education, traditional and modern education, mundane andhereafter education, and so on. So it has an impact on the discussion of the materialon Islamic education that tends to ignore the matters of the mundane, such asscience and technology –that ever mastered by muslims in the heyday of Islamaswell as another matters that actually if we examine the Qur’an as theologicalfoundation, Muslims talk a lot about the cosmology and universality. The newdiscoveries in the field of genetics as a new challenge for the Islamic educationthat still dwell on the issue of teachers professionalism, teaching methodology andfacilities..